HYSTERECTOMY IN PREGNANT WOMEN WITH UTERINE CANCER: AN ANALYSIS UNDER INDONESIAN HEALTH LAW AND UNESCO BIOETHICAL PRINCIPLES - Novenanty, Wurianalya Maria; Innaka, R. A. Antari; Hernawan, Ari (Veritas et Justitia, 2025)
Uterine cancer is commonly treated through hysterectomy, the surgical removal of the uterus. This research examines the legality and bioethical implications of performing a hysterectomy on a pregnant uterine cancer patient, focusing on Indonesian health law and UNESCO Universal Declaration on Bioethics and Human Rights to evaluate whether conducting a hysterectomy on a pregnant uterine cancer patient aligns with Indonesia’s health laws and bioethical principles established by UNESCO. Findings indicate that Indonesian health law does not specifically regulate hysterectomies performed on pregnant uterine cancer patients. However, the law does address abortion in cases of medical emergencies, although Law No. 1 of 2023 lacks detailed criteria for what constitutes such emergencies. Under human rights law, the right to life is non-derogable, both the mother and the fetus (if legally recognized as a child) are entitled to this right. Nonetheless, based on the principles of bioethics, particularly autonomy, beneficence, and non-maleficence, the right to life of the pregnant woman may take precedence, provided she is fully informed, mentally competent, and voluntarily consents to the procedure. In light of these considerations, it is imperative for Indonesia to enact legislation that clearly governs hysterectomy procedures for pregnant cancer patients and to define medical emergencies and the legal status of the fetus more explicitly. Such legal clarity is essential to ensure the consistent protection and promotion of human rights within the Indonesian healthcare system.